Dukungan Sosial Teman Sebaya pada Regulasi Diri Mahasiswa yang Sedang Mengerjakan Skripsi - Meli Meli; Egi Prawita (Universitas Muhammadiyah Purwokerto, 2024)
Completing a final thesis is one of the requirements for students to obtain a bachelor's degree. However, during the process, students often face various challenges that require good self-regulation to complete their thesis within the designated timeframe. This study aims to examine the relationship between peer social support and self-regulation among students working on their thesis. This research employs a quantitative correlational method with purposive sampling as the data collection technique. The participants in this study were students aged 19–25 years, enrolled in semesters 7–12, and currently writing their thesis. Data analysis was conducted using the Spearman Rho correlation test, yielding a p-value of 0.00 (p < 0.05), indicating that the hypothesis was accepted. These findings suggest a significant relationship between peer social support and self-regulation in students working on their thesis. Based on the results, it is recommended that students actively build and utilize peer social support to enhance their self-regulation in overcoming academic challenges. Furthermore, educational institutions should consider providing academic mentoring programs or study groups to help students develop better self-regulation skills, enabling them to navigate obstacles during the thesis-writing process more effectively.